Representasi Trauma dan Perkembangan Tokoh Amora dalam Novel "Fix You" Karya Licoriece Vin - Siti Tarwiayatus Saadah; Vivi Vellanita Wanda Damayanti (Journal of Literature Review, 2026)
This study aims to describe the representation of trauma and the character development of the main character, Amora, in the novel Fix You by Licoriece Vin. The researcher combines Sigmund Freud’s psychoanalytic theory with the concept of Post-Traumatic Growth (PTG). The focus of the study lies in how traumatic experiences from her past life influence the character development and personality dynamics of Amora. Specially, this study pertains to the manifestation of inner conflict, behavior, and decision-making processes in her new life. The research method employed is a qualitative descriptive approach with a hermeneutic focus, which interprets the meanings embedded in Amora’s narrative within the novel Fix You. The research findings indicate that Amora’s trauma is represented through deep guilt. Unforgettable memories, fear, and anxiety, reflecting the dominance of ego-superego conflict within the character’s personality structure. This trauma not only serves as an obstacle to the protagonist’s personality development but also acts as a catalyst for self-awareness and reflection, contributing to Amora’s character transformation toward a more adaptive direction.